The Quality of Customer Service and the Level of Consumer Satisfaction in Timor Leste Telecommunications - Baptista, Marna S. (2020)
The quality of customer services and its resulting consumer satisfaction have greatly contributed to the success of numerous companies, since they constitute competitive advantages, helping companies retaining their costumers and contributing to the company’s recruitment of new clients. Satisfied customers are likely to return and recommend the service to friends and family. The goal of this research was to evaluate perceived service quality and customer satisfaction with the company Timor Telecom. Data was collected through a questionnaire applied to a sample of customers in Dili. The results indicated that customers are globally satisfied with the company and that the most relevant service quality dimensions were: products and services, the company itself, collaborators, and point-of-sale.